Dictators at War and Peace - Weeks, Jessica L. P. (Book collections on Project MUSE., 2014)
Why do some autocratic leaders pursue aggressive or expansionist foreign policies, while others are much more cautious in their use of military force? The first book to focus systematically on the foreign policy of different types of authoritarian regimes, Dictators at War and Peace breaks new ground in our understanding of the international behavior of dictators. Jessica L.P. Weeks explains why certain kinds of regimes are less likely to resort to war than others, why some are more likely to win the wars they start, and why some authoritarian leaders face domestic punishment for foreign policy failures whereas others can weather all but the most serious military defeat. Using novel cross-national data, Weeks looks at various nondemocratic regimes, including those of Saddam Hussein and Joseph Stalin; the Argentine junta at the time of the Falklands War, the military government in Japan before and during World War II, and the North Vietnamese communist regime. She finds that the differences in the conflict behavior of distinct kinds of autocracies are as great as those between democracies and dictatorships. Indeed, some types of autocracies are no more belligerent or reckless than democracies, casting doubt on the common view that democracies are more selective about war than autocracies.